Student attendance online system using barcode reader - Nurul Liyana, Mahmod (2005)
With the Information Technology eras that are really advances nowadays,there a lot of technologies are being used in this century.Several of software created in order to make the data's that saved and access in manual before to the computerize information.The computerize data is more secure because it can protect by password.Thus, one system is developed to solve the problem.The purpose is same as punch card that being used nowadays.The system is used to help the lecturers or staffs on making the student attendance. This system is connected to card reader that are used to save all the student attendance information. The student must bring their Matric Card to the class and scratch it in card reader on making attendance. The Student Attendance System is located in one server which is it can be accessed anytime they like and all the information's are being updated. The lecturer also can print hardcopy by clicking the button that is in the database.Besides, by using this system it can reduce time and can minimize student cheating where by using manually other students also can sign for their friends that is absent that day. The system that will produce is user - friendly and all the instructions using clearly language and easy to understand.